2008
DOI: 10.1149/1.2966179
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Transport Resistant and Electrically Conductive Perovskite Coatings for Solid Oxide Fuel Cell Interconnects

Abstract: Samples of undoped LaMnO 3 ͑LM͒, Sr-doped LaMnO 3 ͑LSM͒, and Ti-doped LaMnO 3 ͑LTM͒ were fabricated by conventional solid-state ceramic processing methods. The objective of Ti doping was to suppress oxygen vacancy concentration/ion transport, while doping with Sr was to enhance oxygen vacancy concentration/ion transport in relation to undoped LM. Total conductivity, mainly electronic, was measured between 500 and 800°C in air. Coatings of LSM, LM, and LTM, 1 m thick, were deposited on Haynes 230 ͑H230͒ foils b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…x = k 1 (time) 0.5 . The parabolic growth law represented a diffusion controlled growth, 19,35 which was valid when the oxide scale layer was dense and well-adhered to the substrate. However, further long-term oxidation for 1200 h formed a thick oxide scale layer of 6-7 um, and caused significant cracking and spallation of the oxide scale.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…x = k 1 (time) 0.5 . The parabolic growth law represented a diffusion controlled growth, 19,35 which was valid when the oxide scale layer was dense and well-adhered to the substrate. However, further long-term oxidation for 1200 h formed a thick oxide scale layer of 6-7 um, and caused significant cracking and spallation of the oxide scale.…”
Section: Resultsmentioning
confidence: 99%
“…Further long-term thermal exposure promoted the chemical interactions between the Cr 2 O 3 scale and the LSM coating, and subsequently formed a thick and continuous (Mn,Cr) 3 O 4 layer on the top of Cr 2 O 3 scale. Since (Mn,Cr) 3 O 4 is thermally more stable than Cr 2 O 3 , [8][9][10][11][14][15][16][17][18][19][20][21][22] the (Mn,Cr) 3 O 4 layer in the outer TGO scale prevented further oxygen inward diffusion to the SS430 and reduced the growth rate of TGO scale, resulting in a sub-parabolic growth rate shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique has been widely used in the solid oxide fuel cell (SOFC) community with some success. [6][7][8][9][10] Komatsu et al 6 demonstrated that La(Ni,Fe)O 3 resists the uptake of Cr from the chromia scale of nickel alloys such as Inconel 600, and Yang et al 7 have shown that (Mn,Co) 3 O 4 -coated Cr22A can successfully be applied to a SOFC cathode material ((La,Sr)FeO 3 ) to create a stable and conducting interface. The specific purpose of this study was to investigate the effectiveness of these barrier materials when applied to the interface between the thermoelectric material Ca 3 Co 4 O 9 and the CroferÒ 22 APU interconnect alloy.…”
Section: Introductionmentioning
confidence: 99%